2014
DOI: 10.7567/jjap.53.09pa03
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of barium titanate nanocube ordered assembly sintered at various temperatures

Abstract: Single-crystalline BaTiO 3 nanocubes were synthesized by a hydrothermal method using a water-soluble titanium complex and surfactants. Ordered assemblies of BaTiO 3 nanocubes were directly fabricated on substrates by the dip-coating method. To optimize the conjugation of the nanocubes, the sintering temperature was changed in the range of 750 to 900 °C to compare with the dielectric properties. The microstructures and dielectric properties of BaTiO 3 nanocube assemblies sintered at various temperatures were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…39), 40) The Pt top electrode was deposited on the assembly by electron beam deposition with a mask (hole diameter 10¯m) and post-annealed at 500°C. The thickness of the top electrode was about 100 nm.…”
Section: Dielectric Properties Of Bt Nc 3d-assembliesmentioning
confidence: 99%
“…39), 40) The Pt top electrode was deposited on the assembly by electron beam deposition with a mask (hole diameter 10¯m) and post-annealed at 500°C. The thickness of the top electrode was about 100 nm.…”
Section: Dielectric Properties Of Bt Nc 3d-assembliesmentioning
confidence: 99%
“…To develop thinner high-performance smartphones and wearable devices, such as eyeglass-type and wristwatch-type, miniaturization and improvement of the properties of dielectric devices such as multilayer ceramic capacitors (MLCCs) are required. An ordered assembly of BaTiO 3 nanocubes (nanocrystals) is a candidate as the main component of such devices [1][2][3][4][5][6][7][8][9][10]. The size of a BaTiO 3 nanocube is about 15 nm, which is much smaller than the typical BaTiO 3 -based particles of about 100 nm in diameter currently used in MLCCs [5,6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocrystals whose size and shape are well-controlled have advantages such as anisotropy, large surface area, and 3D ordered assembly with high packing density and orientation [16][17][18]. We have already reported that 3D assemblies of 15 nm BT nanocube have a high dielectric constant (above 4000) due to the strain induced by interfaces between nanocubes [19][20][21]. Control and design of interfaces is necessary to enhance dielectric and piezoelectric properties.…”
Section: Introductionmentioning
confidence: 99%